Improving the system of motivation and stimulation of the company's personnel - Li, Tianlun (Харківський національний автомобільно-дорожній університет, 2024)
In today's labor market, personnel capable of using new technologies in their work, processing a large amount of information, creating and implementing innovations is a key factor in ensuring the profitability and competitiveness of an enterprise. In this regard, the system of enterprise motivation seems to be the most important component of the management system, which determines the relevance of the chosen topic. The paper considers the theoretical aspects of the personnel motivation system; reveals the specifics and content of outsourcing as a tool for improving the efficiency of enterprise activities; develops a methodological approach to assessing the effectiveness of the personnel motivation system at the enterprise under study, offers recommendations for implementation, and tests the results of the implemented measures.
Keywords: personnel; personnel motivation; outsourcing; analysis; research; effectiveness of the motivation system